PENGARUH MEDIA EDUSPIN DALAM PEMBELAJARAN MATEMATIKA KONTEKSTUAL TERHADAP HASIL BELAJAR SISWA KELAS V DI SDN 101777 SAENTIS PADA MATERI BANGUN DATAR - Clodia Kristy; Elvi Mailani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of EduSpin media in contextual mathematics learning on the learning outcomes of fifth-grade students on the topic of plane figures at SDN 101777 Saentis. This study employed a quantitative approach using a One Group Pretest–Posttest Design. The sample consisted of 19 students selected through a saturated sampling technique. Data were collected using a multiple-choice test and analyzed through descriptive statistics, the normality test, and the Paired Sample t-test using SPSS version 27. The results showed that the mean pretest score increased from 39.47 to 77.63 on the posttest. The normality test indicated that the pretest and posttest data were normally distributed, with significance values of 0.333 and 0.176 (Sig. > 0.05), respectively. Furthermore, the hypothesis test yielded a significance value of 0.001 (Sig. < 0.05), indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that the use of EduSpin media in contextual mathematics learning has a significant effect on the learning outcomes of fifth-grade students on the topic of plane figures at SDN 101777 Saentis.